2006
DOI: 10.1332/030557306777695343
|View full text |Cite
|
Sign up to set email alerts
|

The politics of public expenditure from Thatcher to Blair

Abstract: EnglishThe central concerns of this study are twofold: first, to analyse the nature of the politics of public expenditure under both the Thatcher and Blair governments and to ask whether changes in government did make a difference. Second, to deal with the more general question on whether major differences exist between the Conservative and Labour governments in prioritising public expenditure programmes since 1948. The results confirm differences in public expenditure priorities between the two main parties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In 1988 the Conservatives further de-municipalized social housing by starting large-scale voluntary transfers of council housing into non-profit housing associations (‘voluntary’ as subject to the agreement of a majority of a council’s tenants in a local referendum). These transfers and the right-to-buy involved major disinvestment in social housing, and housing expenditure as a proportion of GDP dropped over the Conservative years and was not reversed until 2000 (Mullard and Swaray, 2006: 498). Currently, the English tenure pattern is council sector (7 percent), housing associations (10 percent) (i.e.…”
Section: Post-war Social Housing Policy In England and Francementioning
confidence: 99%
“…In 1988 the Conservatives further de-municipalized social housing by starting large-scale voluntary transfers of council housing into non-profit housing associations (‘voluntary’ as subject to the agreement of a majority of a council’s tenants in a local referendum). These transfers and the right-to-buy involved major disinvestment in social housing, and housing expenditure as a proportion of GDP dropped over the Conservative years and was not reversed until 2000 (Mullard and Swaray, 2006: 498). Currently, the English tenure pattern is council sector (7 percent), housing associations (10 percent) (i.e.…”
Section: Post-war Social Housing Policy In England and Francementioning
confidence: 99%
“…Keeping health and education spending below the postwar trend rate (Mullard and Swaray 2006), linking long‐term social security benefits to inflation rather than earnings, abolishing earnings‐related unemployment benefit, passing responsibility for sickness benefit to employers and reducing housing subsidies to local authorities produced gradual savings. None the less, increases in unemployment, the transfer of many long‐term unemployed people to Incapacity Benefit and growth in the number of lone parents meant that, over the period 1979 to 1986, public expenditure as a proportion of GDP remained constant.…”
Section: Thatcher's Legacymentioning
confidence: 99%
“…In a previous study, we have suggested that the study of public expenditure by programme reinforced the argument that politics did make a difference. 4 Labour and Conservative government records on public spending did reflect competing political ideologies and policy priorities, with Labour governments spending more on health, housing, education and social security, and Conservative governments spending more on defence and law and order.…”
Section: Introductionmentioning
confidence: 99%